MINIMALLY INVASIVE, HIGH-TECH OPERATIONS FOR LONG TUBULAR BONE FRACTURES IN CHILDREN USING ELASTIC RODS - Omonov Nuriddin Nosirovich; Saidumarov Dilshod Mirzaakhmatovich (Scholar Express Journals, 2023)
Fractures of the long tubular bones in children are among the most severe skeletal injuries. The problem of treatment of fractures of the long bones is still topical at the present stage due to the high frequency of this type of injury, the severity of clinical manifestations, the duration of traditional staged therapy and considerable economic costs. The current views on the choice of optimal tactics of minimally invasive osteosynthesis in long bone fractures of the limb are described in this article. The authors of the article point out the advantages of TEN osteosynthesis in the treatment of fractures of the long bones in children.
Keywords: fractures of long bones in children; minimally invasive osteosynthesis; new technologies